1984
DOI: 10.1021/jo00197a037
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of quaternary ammonium and phosphonium permanganates

Abstract: Trityl bromide was obtained from Aldrich and 6-iodo-l-heptene(1) was prepared from its tosylate and sodium iodide as reported earlier.6 5-Chloro-l-cyclooctene (4), 5-bromo-l-cyclooctene (3), and 5-iodo-l-cyclooctene (2) can be obtained in nearly quantitative yield by Pritzkow's method of adding dry HX to 1,5-cyclooctadiene in CH2C12.13Gas chromatographic analyses were conducted on a Hewlett-Packard Model 700 instrument using a FID detector and packed columns. Quantitative GLC analyses were obtained with the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 2 publications
1
46
0
1
Order By: Relevance
“…The structures of methyltriphenylphosphonium permanganate and n-heptyltriphenylphosphonium permanganate have been reported (Karaman, Barton, Robertson & Lee, 1984). The average Mn---O bond distances in their structures were substantially short [1.47 (2) TETRAETHYLAMMONIUM PERMANGANATE Mn--O bond length in the present structure is 1.610 (6) A which is closer to the reported values for the potassium (Palenik, 1967) and caesium (Prout & Nassimbeni, 1966) …”
supporting
confidence: 83%
“…The structures of methyltriphenylphosphonium permanganate and n-heptyltriphenylphosphonium permanganate have been reported (Karaman, Barton, Robertson & Lee, 1984). The average Mn---O bond distances in their structures were substantially short [1.47 (2) TETRAETHYLAMMONIUM PERMANGANATE Mn--O bond length in the present structure is 1.610 (6) A which is closer to the reported values for the potassium (Palenik, 1967) and caesium (Prout & Nassimbeni, 1966) …”
supporting
confidence: 83%
“…Although most salts exist as discrete ions in aqueous solutions, quaternary ammonium compounds when dissolved in organic solvents are more likely to form ion pairs (11). Brandstrom has shown that the probability of salts existing as ion pairs is inversely dependent on the distance between the centres of the two ions and the dielectric constants of the solvents (20).…”
Section: Resultsmentioning
confidence: 99%
“…Benzyltriethylammonium permanganate was prepared by adding a saturated aqueous solution of KMnO, (4.16 g, 0.0264 mol) dropwise to a stirred solution of benzyltriethylammonium chloride (6.00 g, 0.0264 mol) in 100 mL of water (15). The dark purple precipitate that formed was collected under suction and vacuum dried over phosphorus pentoxide.…”
Section: Methodsmentioning
confidence: 99%